Quality Improvement Initiatives to Reduce Mortality: An Opportunity to Engage Palliative Care and Improve Advance Care Planning. (February 2019) - Flieger, Signe Peterson; Spatz, Erica; Cherlin, Emily J.; Curry, Leslie A.
Background: Despite substantial efforts to integrate palliative care and improve advance care planning, both are underutilized. Quality improvement initiatives focused on reducing mortality may offer an opportunity for facilitating engagement with palliative care and advance care planning. Objective: In the context of an initiative to reduce acute myocardial infarction (AMI) mortality, we examined challenges and opportunities for engaging palliative care and improving advance care planning. Methods: We performed a secondary analysis of qualitative data collected through the Leadership Saves Lives initiative between 2014 and 2016. Data included in-depth interviews with hospital executives, clinicians, administrators, and quality improvement staff (n = 28) from 5 hospitals participating in the Mayo Clinic Care Network. Focused analysis examined emergent themes related to end-of-life experiences, including palliative care and advance care planning. Results: Participants described challenges related to palliative care and advance care planning in the AMI context, including intervention decisions during an acute event, delivering care aligned with patient and family preferences, and the culture around palliative care and hospice. Participants proposed strategies for addressing such challenges in the context of improving AMI quality outcomes. Conclusions: Clinicians who participated in an initiative to reduce AMI mortality highlighted the challenges associated with decision-making regarding interventions, systems for documenting patient goals of care, and broader engagement with palliative care. Quality improvement initiatives focused on mortality may offer a meaningful and feasible opportunity for engaging palliative care. Primary palliative care training is needed to improve discussions about patient and family goals of care near the end of life.